Arsenic trioxide downregulates cancer procoagulant activity in MCF-7 and WM-115 cell lines in vitro - Hoffman, Ewelina A.; Gizelska, Katarzyna; Mirowski, Marek; Mielicki, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2015)
The aim of the study : To analyze human breast cancer cell line MCF-7 and human malignant melanoma cell line WM-115 in order to characterize the cellular expression of CP and to evaluate whether ATO may affect this activity, as well as the viability of the cells. Material and methods : The inhibitory effect of arsenic trioxide on the proliferation of MCF-7 and WM-115 cells were measured with MTT test. The activity of cancer procoagulant after ATO exposure was determined by a specific three-stage chromogenic assay. Results : ATO decreased the CP activity in a dose- and time-dependent manner in MCF-7 cells with no effect on cell proliferation at the same time. However, it affected the CP activity of WM-115 cells in a different way. Reduction in CP activity was followed by an increase after 48 h incubation. The cells viability results showed dose- and time-correlated response within high arsenic concentrations. Conclusions : Arsenic trioxide downregulates the CP expression in human breast cancer and melanoma cells.